Carotid artery disease: AngioCT features - Ferreira, Joana; Miranda, Olinda; Carneiro, Alexandre Lima; Braga, Sandrina; Simões, João Correia; Carrilho, Celso; Mesquita, Amílcar; Cotter, Jorge (Archives of Surgery and Clinical Research, 2019)
The objective of this paper is to emphasis the AngioCT features of carotid dissection/mural hematoma. The image show an internal carotid artery with narrowly eccentric lumen surrounded by a crescent-shaped hypodense mural thickening, with a visibly enhancing vessel wall. The carotid hematoma is a hypodense mural thickening that leads to expansion of the arterial wall, compression of the lumen and release of thrombogenic factors by intimal damage. Hematoma between the intima and media causes vessel expansion diameter and a narrow eccentric lumen. Peripheral hyper density is due to the contrast enhancement of the vasa vasorum in the adventitial layer. The physician should be familiar with the imagiologic features of carotid arterial disease, due to the diferent treatment options.